VARIOUS WAYS TO IMPROVE RUNWAY CAPACITY OF THE NAVOI AIRPORT - Shamsiev, Z.Z.; Saidumarov, I.M.; Boymanov, I.J. (International Journal of Psychosocial Rehabilitation, 2020)
Ensuring the safety of civil aircraft is a major national task for which a huge amount of ma terial resources is spent by the government. Capacity constraints can increase costs for both airlines and passengers, and longer delays can cause inconvenience to passengers. One bottleneck for growth is the terminal area of the capacity. The terminal zone is a controlled airspace in close proximity of the major airports with high traffic volumes. As incoming and outgoing flights share the same airspace, waiting patterns and delays can increase due to the limited number of runways at the airport. One approach to increasing capacity is to expand airports from additional runways. However, the construction of new runways and the opening of new airports not only require large investments, but are also limited by land availability and depend on noise and environmental regulations.The research analyzes the airfield runway's capacity. It reveals its dependence on the accepted organization of air traffic at the airfield, standard arrival routes and runway characteristics of aircraft. The method of estimating the efficiency of the runway use is considered. The analysis of the capacity of Navoi airfield in the Republic of Uzbekistan is carried out.